Foraging and fasting can influence contaminant concentrations in animals: an example with mercury contamination in a free-ranging marine mammal - Daniel P. Costa; Joshua T. Ackerman; Sarah H. Peterson; Daniel E. Crocker (Proceedings of the Royal Society B: Biological Sciences, 2018)
Large fluctuations in animal body mass in relation to life-history events can influence contaminant concentrations and toxicological risk. We quantified mercury concentrations in adult northern elephant seals ( Mirounga angustirostris ) before and after lengthy at sea foraging trips ( n = 89) or fasting periods on land ( n = 27), and showed that mercury concentrations in blood and muscle changed in response to these events. The highest blood mercury concentrations were observed after the breeding fast, whereas the highest muscle mercury concentrations were observed when seals returned to land to moult. Mean female blood mercury concentrations decreased by 30% across each of the two annual foraging trips, demonstrating a foraging-associated dilution of mercury concentrations as seals gained mass. Blood mercury concentrations increased by 103% and 24% across the breeding and moulting fasts, respectively, demonstrating a fasting-associated concentration of mercury as seals lost mass. In contrast to blood, mercury concentrations in female's muscle increased by 19% during the post-breeding foraging trip and did not change during the post-moulting foraging trip. While fasting, female muscle mercury concentrations increased 26% during breeding, but decreased 14% during moulting. Consequently, regardless of exposure, an animal's contaminant concentration can be markedly influenced by their annual life-history events.